Analisis korelasi dan prediksi Pengaruh Kehadiran dan Disiplin terhadap Capaian Akademik Mahasiswa, Studi Kasus Mahasiswa ATS - Musakirawaty; Abdul Tahir; Israkwaty (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This study aims to analyze the influence of attendance, permission, sickness, and discipline on students' Cumulative Grade Point Average (GPA). Consistent attendance in class allows students to follow the subject matter and participate in discussions, potentially increasing GPA. Conversely, permits and illness can interfere with the learning process and negatively impact GPA. Discipline, such as tardiness or inappropriate behavior, can also negatively affect academic performance. This study used Pearson correlation analysis to measure the relationship between independent variables (attendance, permission, illness, discipline) and GPA, as well as linear regression analysis to identify the influence of each factor. Data on attendance, permits, sickness, and discipline were collected from the academic information system for six semesters at one vocational college. The results of the analysis showed that attendance had a strong negative correlation with GPA, while sickness, permitting, and indiscipline also showed a negative relationship with GPA. The linear regression model shows that all these parameters have a negative coefficient to GPA, with permission having the greatest negative influence. This research suggests the importance of policies that encourage consistent attendance and reduce permits and attention to student health and discipline to improve academic achievement.